EFFECTS OF VITAMIN D ADMINISTRATION FOR WOUND HEALING IN PATIENTS WITH DIABETIC FOOT ULCERS: EVIDENCE BASED CASE REPORT - Badralany, Felianty; Nurul Ratna Mutu Manikam (Perhimpunan Dokter Gizi Klinik Indonesia, 2023)
Diabetes mellitus can cause microvascular and macrovascular complications. Diabetic foot ulcer is the complications that often occur in DM patients, which is as much as 10%-25%. In Indonesia, the incidence of diabetic foot ulcers is 12% and DM patients can be at risk of diabetic foot ulcers as much as 55.4%. The mortality rate that occurs as a result of diabetic foot ulcers can reach around 15-30%. Patients who have diabetic foot ulcers significantly decreased vitamin D levels. This study aims to determine the effectiveness of vitamin D supplementation for wound healing in diabetic foot ulcers.